The Role of Family in Handling Negative Emotion and Character Building of Early Childhood - Sri Murni (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2019)
Emotional development of children at an early age needs to get the right stimulation and handling according to the stage of development, the role of the family is very influential on the development of emotions both positive emotions and negative emotions, because the role is very important parents need to recognize emotions themselves before introducing, managing, motivating , and teach children to recognize the emotions of others, giving stimulation and appropriate actions to deal with the emotions that children show early on will determine the character of the child in the future parents can develop children's emotions through routine activities carried out at home and parents must understand the importance of experience for early childhood.